1994
DOI: 10.2105/ajph.84.5.754
|View full text |Cite
|
Sign up to set email alerts
|

Self-reports of HIV risk factors by patients at a sexually transmitted disease clinic: audio vs written questionnaires.

Abstract: OBJECTIVES. The purpose of this study was to determine how the method of assessment affects patient report of human immunodeficiency virus (HIV) risks. METHODS. Patients at a sexually transmitted disease clinic randomly received either a written self-administered questionnaire or an audio self-administered questionnaire delivered by cassette player and headset. These questionnaires were followed by face-to-face interviews. RESULTS. Audio questionnaires had fewer missing responses than written questionnaires. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 15 publications
2
46
0
Order By: Relevance
“…Men reported higher sexual risk taking scores overall and obtained higher scores on the survey format than during the interview. The finding that men reported more risk taking behavior in the survey condition is consistent with previous research that has found that people are more likely to underreport high risk behaviors more frequently in face-to-face interviews than in more anonymous conditions, suggesting the effects of self-presentation concerns (Boekeloo et al, 1994;Siegel, Krauss, & Karus, 1994). However, it must be noted that the effect size for the sex difference in total SRS scores was small.…”
Section: Discussionsupporting
confidence: 89%
“…Men reported higher sexual risk taking scores overall and obtained higher scores on the survey format than during the interview. The finding that men reported more risk taking behavior in the survey condition is consistent with previous research that has found that people are more likely to underreport high risk behaviors more frequently in face-to-face interviews than in more anonymous conditions, suggesting the effects of self-presentation concerns (Boekeloo et al, 1994;Siegel, Krauss, & Karus, 1994). However, it must be noted that the effect size for the sex difference in total SRS scores was small.…”
Section: Discussionsupporting
confidence: 89%
“…Use of audiotaped (cf. Boekeloo et al, 1994) or audio compact disc-administered sexual risk surveys warrants further study. Assessment will remain difficult due to the frailty of memory.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies find that selfadministered instruments, either of the paper and pencil variety or computer assisted, reduce measurement error and tend to produce reports of higher frequencies of sensitive sexual and drug using behaviors than do face-to-face interview methods (Boekeloo et al, 1994;Des Jarlais et al, 1999;Le, Blum, Magnani, Hewett, & Do, 2006;Romer et al, 1997;Simoes, Bastos, Moreira, Lynch, & Metzger, 2006a;Turner et al, 1998). It is thought that higher frequencies of sexual behaviors, particularly stigmatized behaviors, reflect greater validity since adults may seek to manage their public image by underreporting such behaviors (Catania et al, 1990).…”
Section: Introductionmentioning
confidence: 99%